Public Policy Communication for Flood Management - Setiadi Setiadi; Asep Sumaryana; Herijanto Bekti; Dedi Sukarno (The Journal of Society and Media, 2023)
Flood is a hydrometeorological disaster whose intensity and geographic scope continue to increase due to climate change, global warming, and lack of environmental management. Floods often need to be better managed through policy implementation and communication. This study reviews the communication of public policies for flood management. This review uses a traditional approach by referring to previous publications from articles and books, whereas analysis and synthesis refer to the qualitative methods. Public policy must pay attention to fairness, transparency, accountability, participation, and accommodating all parties' interests. The implementation for flood disasters needs to consider elements, the existing programs, and target groups that will receive policies. Flood disaster communication has principles such as transparency, responsiveness, efficiency, effectiveness, accountability, participation, measurement, fairness, and environmental sustainability. Effective and timely communication is very important in dealing with disasters because it can help reduce losses and increase community preparedness. The infrastructure system, which includes drainage, reservoir management, water infiltration zones (green space and densely vegetated land), and mapping of flood-prone areas, must also be communicated adequately. Flood management requires adequate public communication, thus the policy synchronization between different institutions and regions to address socioeconomics and environmental interests within a participatory-based flood management framework